Über die ausstülpbaren Hautblasen der Larven von Gastroidea viridula De Geer und ihre ökologische Bedeutung (Coleoptera: Chrysomelidae). - Renner, Klaus (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The eversible glands of the larvae of Gastroidea viridula are described. Several potential functions of such glands, including similar one of other insects, are discussed. The secretion of the Gastroidea viridula-glands repulses the adults of this species but no enemies. Thus it appears to be mainly a tool of intraspecific regulation.